2018
DOI: 10.1016/j.bbamem.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanism of permeabilization of lecithin liposomes and rat liver mitochondria by the antimicrobial drug triclosan

Abstract: The effect of the antimicrobial compound triclosan (5-chloro-2'-(2,4-dichlorophenoxy)phenol) on the permeability of lecithin liposomes and rat liver mitochondria was studied. It was found that triclosan was able to increase nonspecific permeability of liposomes in a dose-dependent manner, which was detected by the release of the fluorescent probe sulforhodamine B (SRB) from vesicles. A partial release of SRB occurs instantly at the moment of triclosan addition, which is followed by a slow leakage of the dye. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that decreased PPARγ expression or the inhibition of PPARγ activity led to mitochondrial fission, hyperpolarization, and increased oxidative stress [ 50 ]. The PPARγ pathway was one mechanism of triclosan-induced mitochondria-targeted effects, regulating the function of these organelles and the permeability of their membranes [ 51 , 52 ]. Our research showed that PPARγ activation or overexpression mitigated, while PPARγ inhibition or silence aggravated the increase of inflammatory gene expression caused by TCS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that decreased PPARγ expression or the inhibition of PPARγ activity led to mitochondrial fission, hyperpolarization, and increased oxidative stress [ 50 ]. The PPARγ pathway was one mechanism of triclosan-induced mitochondria-targeted effects, regulating the function of these organelles and the permeability of their membranes [ 51 , 52 ]. Our research showed that PPARγ activation or overexpression mitigated, while PPARγ inhibition or silence aggravated the increase of inflammatory gene expression caused by TCS.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, triclosan seems to interfere with mitochondrial respiration through both a protonophoric effect and inhibition of complex II activity leading to apoptotic cell death [ 141 ]. More recently, Belosludtsev et al hypothesised that triclosan can also induce mitochondrial toxicity by membranotropic effects (permeabilization of the plasmatic membrane, production of reactive oxygen species, influx of Ca 2+ ) [ 143 ]. Thus, the synthesis of triclosan analogues with less adverse effects motivated medicinal chemists.…”
Section: Fas-ii Enzymes and Their Corresponding Inhibitorsmentioning
confidence: 99%
“…This inhibition will suppress the membrane phospholipids and the proliferation of microbial cells. TCS has been considered safe for humans and animals since ENR is absent in eukaryotes; however recent studies demonstrate that TCS is considered toxic for eukaryotes [ 30 , 31 ]. It acts primarily on the cytoplasmic membrane and its entry into the cells appears to be by diffusion [ 6 , 23 , 32 , 33 ] due to the lipophilic properties of TCS.…”
Section: Physical and Chemical Properties Of Triclosanmentioning
confidence: 99%
“…This mechanism is known as the TCS membranotropic effect. In 2003, Lygre et al demonstrated that this was the mode of action by which TCS exerts its toxic effect on eukaryotes, destabilizing the membrane of a cell or the mitochondria [ 30 , 31 , 34 ].…”
Section: Physical and Chemical Properties Of Triclosanmentioning
confidence: 99%